The Effect of Ankle Strategy Exercise on Fall Risk Among Older Adults in Gaji Village, Kerek District, Tuban Regency - Riski Nuraini; Dyah Pitaloka; Hyan Oktodia Basuki; Suhartono Suhartono (Jurnal Kesehatan dan Kedokteran, 2026)
Older adults experience physiological decline that reduces balance ability and increases the risk of falls. Falls can lead to serious physical injuries, psychological impacts, decreased quality of life, and even mortality. Therefore, effective and applicable interventions are needed to prevent fall risk, especially in community settings. Objective: This study aimed to determine the effect of ankle strategy exercise on fall risk among older adults in Gaji Village, Kerek District, and to evaluate its role as a community-based nursing intervention. Method: This study employed a quantitative pre-experimental design with a one-group pretest–posttest approach. Participants were selected using purposive sampling based on inclusion criteria. Data were collected using the Berg Balance Scale (BBS) before and after the intervention. Data analysis was conducted using appropriate statistical tests to compare fall risk before and after ankle strategy exercise. Findings: The results showed a significant reduction in fall risk after the intervention. Most participants experienced improved balance performance, indicating that ankle strategy exercise effectively enhances postural stability in older adults. Implications: The findings suggest that ankle strategy exercise can be implemented as a simple, cost-effective, and non-pharmacological intervention in community nursing practice to prevent falls among older adults. This intervention is practical and can be easily adopted in community health programs. Originality: This study provides empirical evidence on the effectiveness of ankle strategy exercise in a rural community setting, highlighting its potential as a feasible and targeted balance training method for fall prevention among older adults.